EDUKASI IBU HAMIL TENTANG HIPEREMESIS GRAVIDARUM MENGGUNAKAN VIDEO EDUKASI DI DESA BIJAWANG KABUPATEN BULUKUMBA - Nursyahraeni Madika Rahman; Ayu Ashari ayu; Aulia Ramadani aulia (JCS, 2023)
Hyperemesis Gravidarum is nausea and vomiting in pregnant women which usually occurs in the morning, but some occur at any time and at night and occurs as a result of changes in the endocrine system that occur during pregnancy, especially the increase in the HCG hormone in pregnancy. Data in Indonesia 50% to 80% of pregnant women experience nausea and vomiting and approximately 5%. Although complaints of nausea, vomiting are considered normal for pregnant women and do not harm the fetus in the womb. However, if the frequency of nausea and vomiting is excessive, you still have to watch out for it. Nausea followed by severe vomiting can be a sign of a disturbance in pregnancy, so education about hyperemesis gravidarum is needed for mothers who experience nausea and vomiting. The purpose of this activity is to provide education about hyperemesis gravidarum. The subject of this community service activity is pregnant women in Bijawang Village, Bulukumba Regency. Community service activities are carried out using the counseling method using educational videos, questions and answers, and discussions. The results of the activity showed that participants were able to understand hyperemesis gravidarum, including the meaning, causes, predisposing factors, and treatment of hyperemesis gravidarum Keywords: Pregnant Women, Hyperemesis Gravidarum, Educational Videos, Counseling